Interrelationships among the MTHFR 677C>T polymorphism, migraine, and cardiovascular disease - Schürks, Markus; Zee, Robert Y L; Buring, Julie E; Kurth, Tobias (Neurology, 2008)
Interrelationships among the MTHFR 677C>T polymorphism (rs1801133), migraine, and cardiovascular disease (CVD) are plausible but remain controversial. Association study among 25,001 white US women, participating in the Women's Health Study, with information on MTHFR 677C>T polymorphism. Migraine and migraine aura status were self-reported. Incident CVD events were confirmed after medical record review. We used logistic regression to investigate the genotype-migraine association and proportional hazards models to evaluate the interrelationships of genotype and migraine on incident CVD. At baseline, 4,577 (18.3%) women reported history of migraine; 39.5% of the 3,226 women with active migraine indicated aura. During a mean of 11.9 years of follow-up, 625 CVD events occurred. Carriers of the TT genotype were less likely to have migraine with aura. The multivariable-adjusted relative risk (RR) in the recessive model was 0.79 (95% CI = 0.65-0.96; p = 0.02). The TT genotype did not increase the risk for CVD. In contrast, migraine with aura doubled the risk for CVD (multivariable-adjusted RR = 2.06; 95% CI = 1.53-2.78; p < 0.0001). Coexistence of migraine with aura and the TT genotype selectively raised this risk (RR = 3.66; 95% CI = 1.69-7.90; p = 0.001). This pattern was driven by a fourfold increased risk for ischemic stroke (multivariable-adjusted RR = 4.19; 95% CI = 1.38-12.74; p = 0.01) and was not apparent for myocardial infarction. Data from this large cohort of women suggest a modest protective effect of the MTHFR 677TT genotype on migraine with aura. The increased risk for cardiovascular disease among migraineurs with aura was magnified for TT genotype carriers, which was driven by a substantially increased risk of ischemic stroke.